Álvaro Lins: leitor de Graciliano Ramos - Rodrigues, Marcos Antonio [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Álvaro Lins (1912-1970) through his critical-journalistic, developed a work that, in the first moment, was restricted more to the biography and psychology of writers. Later, he tries to break free of Impressionism content trend, adopting a scientific character for book review. Thus, we aim in this work approach it as reader of Graciliano Ramos (1892-1953); to this end, has been with analysis fulcrum three written tests on about fiction of Brazilian writer that are compiled in the afterword of Barren Lives (Values and Miseries of Barren Lives): I - Graciliano Ramos in terms of construction of the novel and style art; II - Memories of the novelist explain the nature and kind of his novels; III - Novels, novellas and short stories: vision block of a work of fiction writer. Thus intends to establish a brief outline of the thematic and formal procedures referred by Brazilian reviewer about the prose of the Brazilian novelist, and take into account that he was a pioneer in its reception, accompanied your route so that contributed to their consecration in our literature

Álvaro Lins (1912-1970) por meio de sua crítica-jornalística, desenvolveu um trabalho em que, num primeiro momento, se restringiu mais à biografia e à psicologia dos escritores. Mais tarde, ele procura se libertar da tendência de teor impressionista, passando a adotar um caráter científico para a crítica literária. Desse modo, almeja-se nesse trabalho abordá-lo enquanto leitor de Graciliano Ramos (1892-1953); para tanto, tem-se com fulcro de análise os três ensaios escritos sobre ficção do escritor alagoano que estão compilados no posfácio de Vidas Secas (Valores e Misérias das Vidas Secas): I - Graciliano Ramos em termos de construção do romance e arte do estilo; II - As memórias do romancista explicam a natureza e a espécie dos seus romances; III - Romances, novelas e contos: visão em bloco de uma obra de ficcionista. Intenta-se assim estabelecer um breve delineamento dos procedimentos temáticos e formais evocados pelo crítico pernambucano sobre a prosa do romancista brasileiro, além de levar em conta que ele foi um dos pioneiros na sua recepção, acompanhado seu percurso, de modo que contribuiu para a sua consagração em nossas letras
Keywords: Lins, Alvaro 1912-1970; Ramos, Graciliano 1892-1953; Critica; Jornalismo e literatura; Ficção brasileira - História e crítica - Séc. XX; Brazilian fiction - 20th century - History and criticism